Green synthesis of (R)-3-hydroxy-decanoic acid and analogs from levoglucosenone: a novel access to the fatty acid moiety of rhamnolipids - Petracco, Enzo; Flourat, Amandine L.; Belhomme, Marie-Charlotte; Castex, Stéphanie; Brunissen, Fanny; Brunois, Fanny; Peru, Aurélien A. M.; Allais, Florent; Haudrechy, Arnaud (Frontiers in Chemistry, 2024)
Exhibiting outstanding biosurfactant properties, rhamnolipids (RLs) are highly valuable molecules in the cosmetic, pharmaceutic and agricultural sectors. In the latter, they are used to artificially stimulate natural immune system of crops (also known as elicitation). To decipher their mechanisms of action, readily access natural RLs, and design novel potent elicitors, a straightforward and green access is needed. Herein, starting from cellulose-derived levoglucosenone, we propose an efficient seven-step synthetic pathway to prepare enantiopure (R)-3-hydroxy-fatty acid chains present in RLs with Michael addition, Baeyer-Villiger oxidation, Bernet-Vasella reaction and cross metathesis homologation as key steps (global yield ranging from 24% to 36%).